Development of 3D Design Tutorial Video for Clothing Shape Visualization - Puji Hujria Suci; Reni Fitria; Adriani Adriani; Sri Zulfia Novrita (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This research was the development of a video tutorial for making 3D fashion designs using Marvelous Designer Software which aims to visualize the shape of clothing in real terms. Based on observations, during the fashion practice lectures, students have difficulty understanding the shape of clothing and the fall of fabric in a 2D design, students have not been equipped with knowledge of 3D design making in practical fashion courses. Based on the problems found in the field, research was carried out on the development of learning media in the form of video tutorials for making 3D fashion designs using Marvelous Designer software to visualize the shape of clothing in children's fashion production courses so that students have the ability to make designs and are able to present the shape of clothing and the fall of the fabric used. will be made in 3D. This study uses the 4D Research And Development Model (Define, Design, Develop, Disseminate). The validation of this tutorial video media product was carried out by involving 2 Media Expert validators and 2 Material content validators. This study involved 30 IKK FPP UNP students who took the Children's Clothing Production course.